The Influence of Parity Status on Mother's Behavior in Providing Exclusive Breastfeeding - Dewi Maritalia; Herrywati Tambunan; Anna Malia (Jurnal Kesehatan dr. Soebandi, 2025)
Breast milk is the initial and primary source of nutrition for babies, and exclusive breast milk has been advised by WHO to be given to babies until they are 6 months old. It has been proven that exclusive breastfeeding reduced up to 30,000 infant deaths in Indonesia and 10 million infant deaths in the world. The objective of this research was to discover the effect of parity status on maternal behavior in providing exclusive breastfeeding to babies. This study is quantitative cross-sectional research using purposive sampling technique that involved 100 respondents in total. The research instrument was a questionnaire given to respondent’s door to door. Data processing was carried out univariate and bivariate using linear regression statistical tests. The results of the study showed that the majority of respondents did not provide exclusive breastfeeding amounting to 78% and the majority of parity status was multiparous with a total of 63%. while the results of bivariate analysis with Linear Regression test showed a p-value of 0.015 (α <0.05) indicating that there is an influence of parity status on maternal behavior in providing exclusive breastfeeding. Parity status of mother influences exclusive breastfeeding behavior, with higher parity status showed a reduced likelihood of the mother in providing exclusive breast milk. To increase exclusive breastfeeding coverage, midwives should also promote family planning programs especially to those with higher parity status to encourage exclusive breastfeeding.